Le lauree honoris causa per gli 80 anni dell'Università degli Studi di Firenze - Sandro, Rogari (Firenze University Press, 2005)
On the occasions of the celebrations for the 80th anniversary of Florence University, each Faculty was invited by the Academic Senate to nominate a figure of international standing as recipient of an honorary degree. This book presents the laudatio pronounced by the Deans of the Faculties conferring the laurea honoris causa and the lectio doctoralis given in the Aula Magna of the University by the recipients.